Evaluation of Second Tier Pension Fund Activity Peculiarities in Lithuania and Latvia - Bartkus, Algirdas (Ekonomika, 2007)
The purpose of this paper is to compare the Latvian and the Lithuanian second tier pension systems, to determine the main elements of the second tier pension fund activity, to evaluate the impact of legal regulation, public opinion and investment preferences on the results of Latvian and Lithuanian pension fund activity and activity principles. According to the current legislation, the transitional period of implementation of the 2nd tier of the pension fund system in Lithuania will never end, and there will always be a probability that not all socially insured persons will participate in the 2nd tier of the pension system (in Latvia, about the year 2035, all socially insured persons will participate in the 2nd tier). According to the current legislation, by 2010 about 50% of Latvian funds nominated to pension insurance will be transferred to the 2nd tier of the pension system. That large amount of funds transferred to the 2nd tier implies that the Latvian social insurance system will face a greater risk (than the Lithuanian one) that the social insurance budget will not be capable to finance current benefits. In 2005 and 2006, the Lithuanian pension funds were more profitable facing a higher risk than did Latvian pension funds. The main factor of risk lies in the current Lithuanian legislation and in the possibility to invest 100% of funds in stocks. The less internationally diversified Latvian funds and few possibilities to invest internationally determine the lover profitability of Latvian pension funds and the higher concentration of profitability results of separate pension funds around the market average. The Lithuanian system of pensions is more hazardous than the Latvian.